The Birth of the ASEAN–China Free Trade Area (ACFTA): A Historical Inquiry into China’s Power, Motivations, and Strategies - Luerdi Luerdi (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2026)
ASEAN-China Free Trade Area (ACFTA) has been one of the world’s influential free trade cooperations since its inception in 2010, making the region of Southeast Asia, together with China, a large and dynamic regional market. China acted as an important actor in the formation of the ACFTA. This research sought to deepen China’s role, tracing back to the formation of such cooperation, particularly its economic power, motivations, and strategies driving the free trade cooperation. This research employed a qualitative method with a case study approach and economic liberalization theory. The results indicate that China’s economic power was a major factor for ASEAN member states to agree on the formation of the ACFTA. In addition, China’s motivations and strategies in expanding economic influence aligned with the interests of ASEAN to enhance trade liberalization and regional economic integrity.